Hospital Door Knobs as a Source of Bacterial Contamination: A Study in Iraqi Hospitals - Zainab Salim Jaafar (Institute of Medico-legal Publications Pvt Ltd, 2020)
In this study, 20 swabs were collected from three hospitals in the holy city of Karbala (Al Hussein General Hospital, Al Abbas Private Hospital and Maternity Hospital). Nutrient agar was grown on solid feed medium and incubated at 37 ° C for 24-48 hours for isolation and diagnosis. Bacterial isolates obtained underwent biochemical and bacteriological tests for diagnosis. I prepared different doses of isolated bacteria according to the McFarland model. Then take 0.1 ml of 1/10000 IV dilution and add to Muller Hinton agar medium. The results of the preliminary diagnosis of the isolated bacteria showed that the positive bacteria of Cram stain were higher than those of Cram negative bacteria. The largest number of S.aureus bacteria was in the hospital environment from which swabs were taken and in all locations, especially bathrooms. By calculating the percentage of the total number of samples diagnosed for each hospital separately, the results showed that Hussein General Hospital had the highest contamination rate of 90%, while Al-Ahli Hospital had the lowest contamination rate of 40%. With regard to the effect of antiseptics, the concentration gave 75% Dettol the highest amount of inhibition of bacterial growth compared with other concentrations. On the other hand, the synergistic effect of both antiseptics (Dettol and chlorine) 75% -25% had an effect on inhibition of bacterial growth and its total elimination in the medium compared to other concentrations.